The undercutting of Rosie and Adam - Bannen, Megan (Hart and Mercy series, 2025)
"Immortal demigod Rosie Fox has been patrolling Tanria for decades, but lately, the job has been losing its luster. After one hundred and fifty-seven years of being alive, everything is beginning to lose its luster. When Rosie dies (again) by electrocution (again) after poking around inside a portal choked with shadowy thorns only she can see, she feels stuck in the rut that is her unending life. Thanks to Rosie's meddling, the portal's inventor, Dr. Adam Lee, must come in person to repair the damage. When all the portals begin to break down, he declares an emergency evacuation of Tanria. In the mad rush to get out, Rosie and Adam end up trapped inside the Mist. Together. And uptight Adam Lee in his bespoke menswear seems to know a lot more about what's happening than he lets on.... Rosie is determined to crack the shell of his cool exterior. But the more she learns about Adam, the more she realizes that they both have personal histories as tangled and thorny as the plant that has them trapped inside the Mist. Maybe two people who have found themselves stuck in this life can find a way to unstick each other ... just when their time on this earth seems to be running out"--